Effect Of Light On Squid Behaviour And Its Application For Squid Net Fishing In Malaysia - Hajisamae, Sukree (1996)

(untitled)
This study was carried out with the objectives of understanding the behaviour of squid in response to artificial light, determining the effects of different characters of light on squid net fishing and estimating the distribution pattern of underwater light which is currently employed by Malaysian fishermen. The experiments on squids were conducted in confinement and open waters. The distribution pattern of underwater illuminance was estimated by theoretical model. Experiment in confined floating cage showed the response of big fin reef squid (Sepioteuthis lessoniana) and mitre squid (Loligo chinensis) to the different characters of artificial light. These two species prefer to remain in the underwater illuminance ranging from 1.5 to 22.5 and 1.5 to 25.0 lux, respectively, with the majority of both species occuring at 2.5 to 10.0 lux. However, big fin reef squid demonstrated a considerably stronger phototaxis animal than mitre squid. This was supported by the open water study in which big fin reef squid would swim up to the water surface with active movement, while mitre squid prefer to remain at the sea bottom. Studies on the effect of different characters of artificial lights used by fishermen indicated no significant difference between CPUE and the different types and intensities of fishing lamp. It is recommended that the intensity of light source for Malaysian squid netting boats should be reduced and the present type fishing lamp should be replaced by high pressure mercury lamp. The use of red and white spotlight lamps are also recommended. Results on the estimation of a theoretical model also confirmed that the current usage of attracting light system was in excess of the optimum level of light intensity for Malaysian squid fishing grounds. The efficiency of lamp and the height of light sources installed on the boat should be considered for lighting management.